THE CONSTRUCTION OF HOMOPHOBIAIN A SCREENPLAY ENTITLED 'MILK' - Reviana Rahmania Surya, - (2010)
This research entitled 'The Construction of Homophobia in a Screenplay Entitled Milk' is aimed at investigating homophobic attitudes and how homophobia is constructed as represented in the text. The research employs descriptive analysis, which is qualitative in nature and uses Queer Theory as the theoretical framework. Through the analysis, the research found that homophobic attitudes in 'Milk' are classified into three major distinctions: verbal abuse, non verbal abuse and physical abuse. Verbal abuse is defined into offensive remarks and name calling; non-verbal abuse is divided into discrimination and rejection while physical abuse is categorized into physical attack and threatening behavior. The research also reveals that the homophobia is constructed by the cycle of heteronormativity that distinguished into religion, masculinity and social culture.